2007
DOI: 10.1007/s12070-007-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of underlay tympanoplasty with temporalis fascia and tragal perichondrium

Abstract: The perforations of the tympanic membrane maybe of traumatic origin or due to chronic suppurative otitis media. If the perforations fail to heal conservatively, they require surgical closure. Autologous graft materials have stood the test of time in repairing tympanic membrane perforations. In our tertiary care institution we conducted a prospective randomized control trial on 50 subjects to evaluate the comparative efficacy of temporalis fascia and tragal perichondrium as grafting material in underlay tympano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 6 publications
6
50
2
1
Order By: Relevance
“…Temporalis fascia has its own advantages like a common incision for approach, large amount of graft material is available and more so that its basal metabolic rate is low, its thickness is similar to normal tympanic membrane and embryo logically it develops from mesoderm which is same as normal tympanic membrane [6,17,18]. But temporalis fascia can suffer atrophy or vascularisation, causing posterior shrinkage or sinking in middle ear, ultimately causing failure of closure of the perforation in such cases [19,20]. Cartilage has been used with great success to reconstruct TM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporalis fascia has its own advantages like a common incision for approach, large amount of graft material is available and more so that its basal metabolic rate is low, its thickness is similar to normal tympanic membrane and embryo logically it develops from mesoderm which is same as normal tympanic membrane [6,17,18]. But temporalis fascia can suffer atrophy or vascularisation, causing posterior shrinkage or sinking in middle ear, ultimately causing failure of closure of the perforation in such cases [19,20]. Cartilage has been used with great success to reconstruct TM.…”
Section: Discussionmentioning
confidence: 99%
“…Subtotal perforation with very small anterior remnant of tympanic membrane and anterior bony overhang are more prone to failure after tympanoplasty [7]. Though various methods are practiced for placement of graft in tympanoplasty for Subtotal perforation, failure of perforation to close is seen in 10 % of cases [7,19]. The reasons of residual perforations are poor adaptation of graft, displacement of graft which may sink medially or may shift posteriorly or may shrink.…”
Section: Introductionmentioning
confidence: 99%
“…Retroauricular approach was used in cases where temporalis fascia was required and in one case where the anterior perforation margin could not be viewed through the ear canal. The Underlay technique was used in all cases, as incidence of intratympanic cholesteatoma is less than 1% [7]. The worse-hearing ear was operated first.…”
Section: Surgical Procedures and Follow-upmentioning
confidence: 99%
“…In our study, closure rate of ABG within 10dB was found in 12(30%) cases which is comparable to Singh et.al (63%), Herman and Tang (75%) and Dabholkar et.al (76%), Strahan et.al (82%) and Gupta and Mishra (92%). [8][9][10][11][12] ABG closure between 11-20dB was found in 24 (60%) cases.…”
Section: Discussionmentioning
confidence: 99%